The quality of life of parents of children with autism spectrum disorder: A systematic review - Vasilopoulou, Eleni; Nisbet, Joy (Research in autism spectrum disorders, 2016)
•This study reviewed the literature concerning QoL in parents of children with ASD.•Twelve studies were identified as relevant and included in the analysis.•All studies indicated lower QoL among these parents in at least one domain.•A number of child, parent and contextual variables were associated with QoL. Previous research has raised concerns about the quality of life (QoL) of parents of children with autism spectrum disorder (ASD). A better understanding of parental QoL can inform clinicians and policymakers and lead to improved outcomes for both parents and children. This review aimed to systematically examine studies measuring the QoL among parents of children with ASD (<18 years) and to investigate its parental, child-related and contextual associated factors. An electronic database search was conducted using Medline, Psycinfo, Embase, CINAHL, Biosis, ASSIA, Social Services Abstracts, Sociological Abstracts and Open grey. This review indicated poorer QoL among parents of children with ASD compared to parents of typically developing children or to population norms. Variables associated with lower parental QoL within this group included child behavioural difficulties, unemployment, being a mother and lack of social support. This review verified previous reports on lower QoL among parents of children with ASD and highlighted potential areas of support. Implications for future research, policy and practice are discussed.